Suite Royale: from concept to digital playable - Cai, Xiaoliang (Nanyang Technological University, 2024)
This report explores the designing and production process of the 2d turn based card game project, Suit Royale. It includes the initial concept for the project, various paper prototypes, playtesting feedback, some challenges faced during the production stage.